2002
DOI: 10.1159/000048355
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome following Traumatic Brain Injury in Young Children

Abstract: The relationship between clinical and neuroimaging variables and multiple outcome measures was examined in a longitudinal, prospective study of 60 children less than 6 years of age who sustained either inflicted or noninflicted traumatic brain injury. Hierarchical multiple regression indicated that the modified Glasgow Coma Scale score, the duration of impaired consciousness and the number of intracranial lesions visualized on CT/MRI accounted for a significant amount of the variance in the Glasgow Outcome Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 27 publications
(64 reference statements)
7
65
0
1
Order By: Relevance
“…33,34 One other study recently found age not to be predictive of outcome in young children, and here the authors comment that their findings are "contrary to expectations." 35 A larger study is required to confirm our findings that age does not seem to influence outcome within the subpopulation of inflicted TBI. A major determinant of outcome in young children is the cause of the TBI.…”
Section: E182mentioning
confidence: 61%
See 1 more Smart Citation
“…33,34 One other study recently found age not to be predictive of outcome in young children, and here the authors comment that their findings are "contrary to expectations." 35 A larger study is required to confirm our findings that age does not seem to influence outcome within the subpopulation of inflicted TBI. A major determinant of outcome in young children is the cause of the TBI.…”
Section: E182mentioning
confidence: 61%
“…A major determinant of outcome in young children is the cause of the TBI. 35 It is not surprising that the external evidence of impact did not correlate with outcome as it is acknowledged that external evidence of impact does not determine that impact did not occur. 36 The main factors that did correlate with outcome were the severity of injury as assessed by the PTS and the GCS.…”
Section: E182mentioning
confidence: 99%
“…In addition, persistent neurologic damage was found to be related to younger age, prolongation of consciousness state, child trauma score and Glaskow coma score, subdural hemorrhage, decreased pressure in the brain/decreased intravascular pressure and presence of brain edema (16,53,56).…”
Section: Prognosismentioning
confidence: 99%
“…22 In 1972 while addressing the issue of prevention Caffey wrote 41 : "Hark ye, good parents, to my words true and plain, Box 1: Key principles in emergency management of the unconscious infant when the cause is unknown…”
Section: Outcome and Preventionmentioning
confidence: 99%